2023
DOI: 10.3390/ma16093302
|View full text |Cite
|
Sign up to set email alerts
|

The Failure Mechanical Properties of Cemented Paste Backfill with Recycled Rubber

Abstract: Understanding the mechanical properties and failure process of cemented paste backfill with recycled rubber (RCPB) is the foundation of backfill design in underground mining. In this study, physical and mechanical tests were conducted on RCPB to obtain its mechanical property parameters, such as its uniaxial compressive strength (UCS), toughness, and peak strain. The influence of the rubber dosage on the mechanical properties of RCPB was also analyzed. In addition, the deformation behavior, fracture developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…They found that adding 0.6 wt% RTPF to a CTB yielded a comparable mobility and strength to an enhanced CTB with 0.3 wt% PPF, while reducing costs and improving sustainability. With the rapid development of the auto industry, the environmental issues caused by discarded automotive tires, known as "black pollution," urgently need to be addressed [14][15][16]. Recycled rubber is the main means to solve the issue of discarded tires.…”
Section: Introductionmentioning
confidence: 99%
“…They found that adding 0.6 wt% RTPF to a CTB yielded a comparable mobility and strength to an enhanced CTB with 0.3 wt% PPF, while reducing costs and improving sustainability. With the rapid development of the auto industry, the environmental issues caused by discarded automotive tires, known as "black pollution," urgently need to be addressed [14][15][16]. Recycled rubber is the main means to solve the issue of discarded tires.…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars and engineers have so far performed numerous investigations on CTB's toughness improvement [31,32]. The main method to enhance the toughness of CTB materials is to incorporate different additives such as straw [33], rubber [34], fiber [32], sand [35], and others [36,37]. Researchers have improved the crack resistance and toughness of engineering specimens by adding hybrid fibers to CTB (i.e., strengthening fill's strength features and enhancing the material's stress-crack rupture link, [38][39][40]).…”
Section: Introductionmentioning
confidence: 99%